MRE11A and SKP2 genes are associated with the increased cytotoxicity induced by the synergistic effects of cisplatin and gemcitabine in bladder cancer cells - Silva, Glenda Nicioli da [UNESP]; Camargo, Elaine Aparecida de [UNESP]; Ventura Savio, Andre Luiz [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Springer, 2014)
The combination of gemcitabine and cisplatin has been shown previously to elicit a synergistic therapeutic effect on bladder cancer cell lines and result in reduced cell survival. However, the precise mechanism by which cells die has not been elucidated. Cell cycle-related genes are the predominant targets of chemotherapeutic protocols. Therefore, molecular biomarkers that are predictive of therapeutic outcomes associated with tumor sensitivity might be important for optimal treatment protocol selection. The aim of this study was to investigate the changes in gene expression in cell cycle-related genes that were induced by cisplatin, gemcitabine or a combined treatment using both agents in a low-grade urinary bladder transitional carcinoma cell line (RT4). The following three treatment protocols were used: 1.0 mu M cisplatin, 1.56 mu M gemcitabine and a combination of 1.0 mu M cisplatin and 1.56 mu M gemcitabine. Cytometry and morphology analysis (by phase-contrast photomicrography) were performed in addition to pathway-specific gene expression analysis using quantitative RT-PCR gene arrays. The following results were observed after 1.0 mu M cisplatin treatment: (1) a decrease in cell number, (2) an increased percentage of scattered cells and (3) downregulated expression of genes related to cell cycle arrest, G1/S-to-mitotic cell cycle transition, DNA repair, apoptosis, transcription and mitosis. Treatment with 1.56 mu M gemcitabine, or with both drugs simultaneously, induced the following effects: (1) a decrease in cell number, (2) an increased percentage of scattered and elongated cells, (3) the modulation of genes that are predominantly involved in DNA repair and (4) a significant upregulation of genes related to cell cycle arrest. Reduced cell density was observed after the combined treatment compared to the two other single-agent protocols. The downregulation of MRE11A and SKP2 was observed only in cells subjected to the combined treatment. In conclusion, cisplatin, gemcitabine and the combination of both drugs elicited distinct toxicogenomic effects in the RT4 bladder transitional carcinoma cell line, although disruptions in the expression of cell cycle control-related genes and other pathways responsible for cell survival were observed for all of the protocols. MRE11A and SKP2 downregulation appeared to be responsible for the synergistic therapeutic effects elicited by cisplatin and gemcitabine.
Keywords: Cisplatin; Gemcitabine; Gene expression profiling; RT4 cell line